Amplification of The GAPDH Gene from The Urine eDNA of Sumatran Rhino in Sumatran Rhino Sanctuary, Way Kambas National Park - Priyambodo Priyambodo; Chicka Refina P. Putri; Elly L. Rustiati; Yeyen Kurniawati; Danisworo Zulkarnain; Dian Neli Pratiwi; Zulfi Arsan; Giyono Giyono; Ganis Mustikawati; Vindo R. Pertiwi; Sukatmoko Sukatmoko; Eko A. Srihanto; Enny Saswiyanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Profiling the genetic character of each individual sumatran rhino is important in order to maintain individual viability and genetic variability of Sumatran rhinos. Non-invasive sampling is needed to minimize the disturbance of individual sumatran rhinos, this is due to the solitary character of sumatran rhinos and tend to be afraid to interact with humans. Until now, non-invasive sampling of sumatran rhinos in Way Kambas National Park (WKNP) has only been done through the source of the puddle. This study aims to amplify the GAPDH gene from sumatran rhino environmental DNA (eDNA) sourced from urine. Urine sampling was carried out on four of the eight sumatran rhino individuals in WKNP. DNA extraction of four sumatran rhino urine samples was carried out with reference to the DNeasy® Blood & tissue kit extraction protocol. Amplification of eDNA extraction results was carried out by polymerase chain reaction (PCR) using GAPDH primers. Visualization of extraction and amplification results from four individual sumatran rhinos at TNWK was tested qualitatively with 1% agarose gel electrophoresis. Electrophoresis results showed positive results after amplification of four individual sumatran rhino urine samples at sizes between 100-200bp. This study successfully amplified the GAPDH gene from four sumatran rhino individuals in WKNP based on qualitative tests. In further conservation efforts, it is necessary to explore eDNA extraction from other potential sources.